Strategi Membangun Kualitas Madrasah dalam Meningkatkan Kepercayaan Masyarakat terhadap Pendidikan Islam di MI Tarbiyatul Islamiyah Tenggur Rejotangan Tulungagung - Suprihno Suprihno; Eti Rohmawati (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
Islamic education in Indonesia has experienced ups and downs. The digital era has changed children towards individualism, losing the world of playing with nature. Even Islamic education has found a steep way to progress and develop, one of which is public distrust of Islamic educational institutions which is getting lower. So it is very important to analyze what happened. Based on the above, this paper formulates marketing management strategies, quality improvement procedures and builds public trust in Islamic educational institutions based on research results at MI Tarbiyatul Islamiyah Tenggur Rejotangan Tulungagung. Qualitative research conducted by researchers using field study methods, in the form of observation, interviews, and documentation, data collection by data condensation, data presentation and conclusions. Produces findings that Islamic education is actually not limited to the process of educating only, but includes the process of changing behavior. Strategies are needed to build public trust in Islamic education, namely: school review, formulating vision, mission, strategies and work programs, expanding participatory leadership, intervention at various levels, developing the culture of educational institutions, improving teacher capabilities, mobilizing funding sources, monitoring, evaluating and controlling.